Supply Chain Networks Optimization under Uncertain Environment with Dhouib-Matrix-TP1 heuristic - Dhouib, Souhail; Kammoun, Manel; Dhouib, Saima; Loukil , Taicir (Statistics, Optimization & Information Computing, 2025)
The transportation problem (TP) is a critical component of the supply chain network that involves determining the most efficient way to move goods from one location to another. TP is a generic name given to a whole class of problems in which diverse types of transportation modes are used to supply a product from sources to destinations. The TP is a common challenge in supply chain networks, where it aims to minimize the total cost of transportation to satisfy both supply and demand constraints. In this paper, the constructive heuristic Dhouib-Matrix-TP1 (DM-TP1) is adapted in order to solve the balanced and unbalanced TP with heptagonal fuzzy numbers. DM-TP1 needs a reduced number of iterations in order to generate a good initial basic feasible solution and uses a novel metric based on (Average-Min). Several numerical examples (balanced and unbalanced) are used to prove the performance of DM-TP1.